Sensitivity of human meningioma cells to the cyclin-dependent kinase inhibitor, TG02 - Achenbach, Caroline von; Le Rhun, Emilie; Sahm, Felix; Wang, Sophie S.; Sievers, Philipp; Neidert, Marian C.; Rushing, Elisabeth J.; Lawhon, Tracy; Schneider, Hannah; Deimling, Andreas von; Weller, Michael (Translational oncology, 2020)
Standards of care for meningioma include surgical resection and radiotherapy whereas pharmacotherapy plays almost no role in this disease. We generated primary cultures from surgically removed meningiomas to explore the activity of a novel cyclin-dependent kinase inhibitor, TG02, in meningioma cell cultures. Tumor and cell cultures were characterized by mutation profiling and DNA methylation profiling. DNA methylation data were used to allot each sample to one out of six previously established meningioma methylation classes: benign (ben)-1, 2, 3, intermediate (int)-A, B, and malignant (mal). Four tumors assigned to the methylation class ben-2 showed the same class in culture whereas cultures from five non-ben-2 tumors showed a more malignant class in four patients. Cell cultures were uniformly sensitive to TG02 in the nanomolar range. Assignment of the cell cultures to a more malignant methylation class appeared to be more closely associated with TG02 sensitivity than assignment to a higher WHO grade of the primary tumors. Primary cell cultures from meningioma facilitate the investigation of the anti-meningioma activity of novel agents. TG02, an orally available cyclin-dependent kinase (CDK) inhibitor, warrants further exploration.